2023
DOI: 10.3390/ijms24076476
|View full text |Cite
|
Sign up to set email alerts
|

High Expression of Tetraspanin 5 as a Prognostic Marker of Colorectal Cancer

Abstract: Cancer is a major disease and the leading cause of death worldwide, with colorectal cancer (CRC) being the third-most common cancer in Korea. The survival rate associated with CRC reduces as the disease stage increases. Therefore, its early detection and treatment can greatly increase patient survival rates. In this study, we identified the tetraspanin 5 (TSPAN5) gene as an important biomarker for predicting the prognosis of patients with CRC. A TMA slide was used for statistical analysis. pN and clinical stag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 23 publications
(26 reference statements)
0
1
0
Order By: Relevance
“…By forming protein complexes with various cell surface molecules, such as integrins and receptors, tetraspanins participate in the progression and metastasis of various cancers, including CC (Scheme S1, Supplementary File S1) [5,7,8]. In CC, various studies have shown specific expressions of some tetraspanins in CC cell lines and bulk tissues, indicating their potential as diagnostic markers and therapeutic Life 2024, 14, 126 2 of 16 targets [7,9,10]. Some tetraspanins, such as TSPAN8 and CD151, have been associated with advanced tumor stage, metastasis, and poor clinical outcomes [7,11,12].…”
Section: Introductionmentioning
confidence: 99%
“…By forming protein complexes with various cell surface molecules, such as integrins and receptors, tetraspanins participate in the progression and metastasis of various cancers, including CC (Scheme S1, Supplementary File S1) [5,7,8]. In CC, various studies have shown specific expressions of some tetraspanins in CC cell lines and bulk tissues, indicating their potential as diagnostic markers and therapeutic Life 2024, 14, 126 2 of 16 targets [7,9,10]. Some tetraspanins, such as TSPAN8 and CD151, have been associated with advanced tumor stage, metastasis, and poor clinical outcomes [7,11,12].…”
Section: Introductionmentioning
confidence: 99%